2018
DOI: 10.1039/c8cc00914g
|View full text |Cite
|
Sign up to set email alerts
|

A selective glucose sensor: the cooperative effect of monoboronic acid-modified poly(amidoamine) dendrimers

Abstract: Selective glucose binding was identified through five generations of monoboronic acid-functionalized PAMAM dendrimers. The best selectivity obtained when using G3 dendrimers (1b) generated 71.1, 94.9, and 1309 times stronger binding than when using galactose, fructose, and lactose, respectively. Further experiments using dendrimer analogues and glucose derivatives suggested that two nearby monoboronic acids cooperatively bound one glucose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Dendrimers are a class of well-defined nanostructured macromolecules consisting of three critical architectural domains: the multivalent surface, the interior shells surrounding the core, and the core. These domains can be tailored for a specific purpose, such as a dendritic sensor [ 222 , 223 ] or a payload carrier, the encapsulation of molecules in their interior shell being the most used application of dendrimers [ 224 , 225 ]. One of the most common dendrimers is based on the chemical structure poly (amidoamine) (PAMAM), which has a large number of reactive amine groups on the periphery, making them an excellent platform to construct nanomaterials for biomedical applications [ 226 228 ].…”
Section: Functionalization Of Ionpsmentioning
confidence: 99%
“…Dendrimers are a class of well-defined nanostructured macromolecules consisting of three critical architectural domains: the multivalent surface, the interior shells surrounding the core, and the core. These domains can be tailored for a specific purpose, such as a dendritic sensor [ 222 , 223 ] or a payload carrier, the encapsulation of molecules in their interior shell being the most used application of dendrimers [ 224 , 225 ]. One of the most common dendrimers is based on the chemical structure poly (amidoamine) (PAMAM), which has a large number of reactive amine groups on the periphery, making them an excellent platform to construct nanomaterials for biomedical applications [ 226 228 ].…”
Section: Functionalization Of Ionpsmentioning
confidence: 99%
“… 12 Currently, results indicated that the size of the dendrimer is a decisive factor in their selective binding to glucose. 13 However, the binding mechanism for selective affinity to a given carbohydrate remains unclear. 14 The requirement of boronic acids’ allocation was not studied well due to the difficulty of synthesizing the designed products.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Boronic acids are well-known to have affinity for the diol groups of carbohydrates; however, binding selectivity between sugars is often poor and binding affinity is often prohibitively weak in water. The multivalency of PAMAM dendrimers modified with boronic acid groups has been shown to mitigate this limitation. , In these examples, the fluorescent dyes alizarin red S (ARS) and 4-methylesculetin (ML), which show a significant increase in QY upon complexation with boronic acids, enabled PL-based signaling with the dendrimer. One study showed that cooperative binding between two boronic acid groups on a G3 PAMAM dendrimer enabled detection of glucose (in organic solvent) with high selectivity (between 70- and 1300-fold) versus other sugars .…”
Section: Chemical Analysis and Bioanalysismentioning
confidence: 99%
“…The multivalency of PAMAM dendrimers modified with boronic acid groups has been shown to mitigate this limitation. , In these examples, the fluorescent dyes alizarin red S (ARS) and 4-methylesculetin (ML), which show a significant increase in QY upon complexation with boronic acids, enabled PL-based signaling with the dendrimer. One study showed that cooperative binding between two boronic acid groups on a G3 PAMAM dendrimer enabled detection of glucose (in organic solvent) with high selectivity (between 70- and 1300-fold) versus other sugars . In another study, a fluorescent array was developed with G3 PAMAM dendrimers modified with either o - or m -boronic acids, with either ARS or ML as a fluorescent reporter, and measured at one of two pH conditions (Figure ).…”
Section: Chemical Analysis and Bioanalysismentioning
confidence: 99%